Platelet Activation Markers in Patients with Peripheral Arterial Disease - Gresele, Paolo; Catalano, Mariella; Giammarresi, Carlo; Volpato, Raul; Termini, Rosanna; Ciabattoni, Giovanni; Nenci, Giuseppe G; Davì, Giovanni (Thrombosis and Haemostasis, 1997)
Peripheral vascular disease (PVD) is an indicator of diffuse atherosclerosis and is associated with a greatly increased incidence of coronary heart and cerebrovascular disease. Although several studies have assessed whether in vivo platelet activation takes place in patients with PVD, no data are available comparing different platelet function tests in this patient population.We have compared prospectively four tests for the measurement of in vivo platelet activation (plasma βTG, plasma PF4, intraplatelet (βTG and urinary excretion of 11-dehydro-TXB2) and one in vitro platelet function test (ADP-induced platelet aggregation) in 63 well-characterized patients with intermittent claudication and in 18 age- and sex- matched healthy volunteers.No statistically significant difference was found between patients and controls for plasma βTG (20.0 ± 11.8 vs. 18.8 ± 9.0 ng/ml, respectively), plasma PF4 (5.2 ± 2.9 vs. 6.3 ± 3.5 ng/ml), βTG/PF4 ratio (4.0 ± 2.9 vs. 3.6 ± 1.8), intraplatelet pTG (4503 ± 1482 vs. 4059 ± 1065 ng/ml), and threshold aggregatory concentration of ADP (1.7 ± 0.72 vs. 1.45 ± 0.56 μM).Urinary 11-dehydro-TXB2 was instead significantly higher in the PVD group (55.4 ± 27.5 vs. 26.7 ± 7.0 ng/h, p <0.001).Our study shows that urinary 11-dehydro-TXB2 is a more sensitive index of in vivo platelet activation than the measurement of either platelet specific proteins or of in vitro platelet aggregation in patients with PVD.